New Insights into Molecular Ehrlichia chaffeensis-Host Interactions - Wakeel, Abdul (2010)
Ehrlichia chaffeensis is an obligately intracellular bacterium that exhibits tropism for mononuclear phagocytes and survives by reprogramming the host cell. Here we review new information regarding the newly characterized effector molecules and the complex network of molecular host-pathogen interactions that the organism exploits enabling it to thrive and persist intracellularly.